2012
DOI: 10.1136/jmedgenet-2012-100868
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies aCOL14A1mutation in a large Chinese pedigree with punctate palmoplantar keratoderma

Abstract: The power of combining exome sequencing and linkage information in the study of genetics of autosomal dominant disorders, even in simplex cases, has been demonstrated. Our results suggested that COL14A1 would be a casual gene for PPPK, which was helpful for advancing us on understanding of the pathogenesis of PPPK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Recently, PPPK has been reported to be caused by mutations in two genes: collagen, type XIV, α1 ( COL14A1 ) and AAGAB . The latter encodes α‐ and γ‐adaptin‐binding protein p34 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, PPPK has been reported to be caused by mutations in two genes: collagen, type XIV, α1 ( COL14A1 ) and AAGAB . The latter encodes α‐ and γ‐adaptin‐binding protein p34 …”
Section: Discussionmentioning
confidence: 99%
“…Gao et al 5 and Mama€ ı et al 6 refined localization of a PPPK gene to a region at 15q22.2-15q22.31 and a locus to only 0Á967 Mb at chromosome 15, respectively. Recently, Guo et al 7 identified a missense mutation (c.4505C>T) in the gene collagen, type XIV, a1 (COL14A1) in a large Chinese family with PPPK. Mutations in aand c-adaptin-binding protein p34 (AAGAB) were also identified in patients with PPPK from Germany and the U.K. 8,9 In this study, we found a novel mutation responsible for PPPK in two Chinese families.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 1 more Smart Citation
“…Monoallelic mutations have been described in the AAGAB gene encoding for the alpha‐ and gamma‐adaptin‐binding protein p34 . Recently, a heterozygous mutation in the COL14A1 gene, encoding for the collagen type XIV, has been detected in a four‐generation Chinese family first described by Zhang et al …”
Section: Isolated Palmoplantar Keratodermasmentioning
confidence: 99%
“…Punctate PPK (PPKP) features multiple hyperkeratotic papules that develop in early adolescence or later, and are irregularly distributed on the palms and soles . The disease is clinically classified into three autosomal dominant subtypes: PPKP1 (OMIM #148600, 614936), characterized by multiple tiny punctate keratoses and caused by mutations in AAGAB or COL14A1 ; PPKP2 (OMIM #175860), which features tiny hyperkeratotic spinous papules; and PPKP3, or acrokeratoelastoidosis (AKE; OMIM #101850), which manifests with small hyperkeratotic papules located over the peripheral margins of the palms and soles, and is typically associated with degeneration of elastic fibres on histology . The molecular aetiology of PPKP2 and AKE remains unknown.…”
mentioning
confidence: 99%